2014
DOI: 10.1186/1476-511x-13-26
|View full text |Cite
|
Sign up to set email alerts
|

Oligofructose supplementation during pregnancy and lactation impairs offspring development and alters the intestinal properties of 21-d-old pups

Abstract: BackgroundPreviously, we showed that the intake of trans fatty acids during pregnancy and lactation triggers a pro-inflammatory status in the offspring. On the other hand, prebiotics can alter the intestinal environment, reducing serum lipopolysaccharides (LPS) concentrations. This study evaluated the effect of the oligofructose 10% diet supplementation in the presence or absence of hydrogenated vegetable fat during pregnancy and lactation on the development, endotoxemia and bacterial composition of 21-d-old o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
8
2
Order By: Relevance
“…Although only pups from the CF group showed elevated serum endotoxemia in a previous study [ 24 ], in this study, the 21-d-old offspring of the TF group presented with higher p-NFκB p65 protein levels in the liver ( Fig 3D ) and an increased serum concentration of TNF-α ( Fig 1 ). Gene and protein expressions of TLR4 were not altered in different tissues (Figs 2A , 3A , 4A and 5A ); however it is known that the TLR4 signaling pathway includes the NF-κB activation [ 33 ], which requires the NF-κB p65 subunit phosphorylation and others post-translational modifications [ 34 ].…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Although only pups from the CF group showed elevated serum endotoxemia in a previous study [ 24 ], in this study, the 21-d-old offspring of the TF group presented with higher p-NFκB p65 protein levels in the liver ( Fig 3D ) and an increased serum concentration of TNF-α ( Fig 1 ). Gene and protein expressions of TLR4 were not altered in different tissues (Figs 2A , 3A , 4A and 5A ); however it is known that the TLR4 signaling pathway includes the NF-κB activation [ 33 ], which requires the NF-κB p65 subunit phosphorylation and others post-translational modifications [ 34 ].…”
Section: Discussioncontrasting
confidence: 46%
“…However, in a recent study, we showed an increased LPS serum concentration and genomic DNA levels of lactobacillus spp. in colonic feces from the CF pups, indicating that the maternal intake of a diet supplemented with 10% OF during pregnancy and lactation may lead to changes in intestinal permeability and in bacterial composition, possibly influencing endotoxemia and the LPS-stimulated inflammatory responses in the 21-d-old offspring [ 24 ]. In fact, we also observed that diet supplementation with oligofructose (10%) during pregnancy and lactation caused diarrhea in dams (CF and TF groups) and changed the maternal body weight and food intake among the four experimental groups (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This concept is supported by many studies that have shown that malnutrition, toxins, smoking and maternal diseases during pregnancy affect the birth weight of the offspring, resulting in an aberrant response of the cardiovascular and metabolic system in later life. [2][3][4][5] Furthermore, the opposite situation of increased birth weight or macrosomia also contributes to metabolic programming and later-life morbidity, primarily via altered body composition at birth. [6][7][8] Preeclampsia is a pregnancy-associated disorder, usually complicated with fetal growth restriction and affects 3-7% 9 of the population worldwide.…”
Section: Introductionmentioning
confidence: 99%